Pleural Lubrication - Cristina Porta; Chiara Sironi; Francesca Bodega; Emilio Agostoni (Lubricants, 2016)
During breathing, the pleural surfaces slide against each other continuously without damage. Pleural liquid and lubricating molecules should provide the lubrication of the sliding surfaces, thus protecting the mesothelium from shear-induced abrasion. D’Angelo et al. (Respir. Physiol. Neurobiol. 2004) measured the coefficient of kinetic friction (μ) of rabbit parietal pleura sliding against visceral pleura in vitro at physiological velocities and under physiological loads; it was ~0.02 and did not change with sliding velocity, consistent with boundary lubrication. μ in boundary lubrication can be influenced by surface molecules like hyaluronan, sialomucin or surface active phospholipidis. Hyaluronan or sialomucin is able to restore good boundary lubrication in damaged mesothelium. Nevertheless, hyaluronidase and neuraminidase treatment of the mesothelium does not increase μ, though neuraminidase cleaves sialic acid from the mesothelium. Short pronase or phospholipase treatment, so as to affect only the mesothelial glycocalyx, increases μ, and this increase is removed by hyaluronan or sialomucin. On the other hand, addition of phospholipids after phospholipase treatment produces a small effect relative to that of hyaluronan or sialomucin, and this effect is similar with unsaturated or saturated phospholipids. In damaged mesothelium, the lubrication regimen becomes mixed, but addition of hyaluronan or sialomucin restores boundary lubrication.